Ecclesiastes 3.1-15: Another Interpretation - Blenkinsopp, Joseph 1927- (1995)
The article advances the hypothesis that the 'catalogue of times' in Eccl. 3.2-8 is the longest of the passages cited but not authored by Qoheleth to which the latter has added a title and a brief commentary. Comparison with the ethical teaching of the early Stoics (Zeno, Cleanthes, Chrysippus), especially with respect to the concept of eukairia (timely action), suggests further that the quotation is from a stoicizing Jewish sage. An understanding of 'et lamût (v. 2) as referring to the timely putting an end to one's life would, in addition, be consistent with the teaching of the early Stoa on suicide as a morally permissible act.